Marketing Mix Factors Influence the Purchasing Decision Process of Art Toys among Consumers in Prawet District, Bangkok - อินทกาศ ปณียา; มหาเรือนขวัญ ทัศวรรณ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This study aims to examine the marketing mix factors that influence the decision-making process of purchasing Art Toys among consumers in Prawet District, Bangkok. The sample group consists of 385 individuals who have experience purchasing Art Toys and reside in Prawet District, Bangkok. A non-probability sampling method, specifically purposive sampling, was used. Data were collected using a questionnaire and analyzed using descriptive statistics, including mean and standard deviation, as well as hypothesis testing through multiple regression analysis. The results of the study indicate that the majority of respondents are female, aged between 21-30 years, hold a bachelor’s degree, work as private-sector employees, and have a monthly income between 15,001 and 25,000 Baht. They primarily purchase keychain-type Art Toys, mainly for collection purposes, with a frequency of 1-2 times per month. The key decision-makers in the purchase are the consumers themselves. The marketing mix factors, including product, price, distribution, and promotion, all significantly influence the decision-making process of purchasing Art Toys in Prawet District, Bangkok, with statistical significance at the 0.05 level.